Edmodo Based E-Learning as a Media of Construction Building Learning - Putu Diah Untari Ningsih, Ni; Bruri Triyono, Mochamad; Dahar Minghat, Asnul; Ahmad, Adnan (International Journal of Engineering and Technology, 2018)
Edmodo based E-Learning is a social learning platform for teachers/lecturers, students or for parents that developed in late 2008 by Nic Borg and Jeff O "Hara Edmodo based E-Learning developed based on the principles of group based on class management and also social media. Edmodo based E-Learning is very comprehensive because access is faster and easier to use by using some of the features that function like course management systems. The learning process using teaching materials with Edmodo based E-Learning can be used as a reference in developing appropriate teaching materials for other materials to increase the level of thinking probabilistic learners. Edmodo is certainly a good choice for learning in the fourth industrial revolution era. This study is a literature that tries to express the ideas associated with the use of Edmodo based E-Learning in Building Construction Learning. This study has the following objectives: (1). Describe criteria of Edmodo based E-Learning that good. (2). Describe the material in accordance with the Edmodo based E-Learning in Building Construction learning. (3). Describing the use of Edmodo based E-Learning in Building Construction learning.Â  Â